Parenting Knowledge and Anxiety among Primiparus Couple in Odisha, India: A Cross Sectional Study - Manisha Praharaj; Kshirabdhi Tanaya (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Turning into the parent bring difficulties, challenges and series of changes such as emotionaladjustment, couple relationship issues and trouble overseeing regular newborn child practices. Preparingfor the progress to parenthood brings changes in life roles and finding a way to oversee such changes. Newparents can get ready for parenthood by training of skills, child rearing tasks and assets that can help withturning into a parent.Objective: To evaluate the level of knowledge of primigravida mother and father regarding parenthood. Todetermine the level of anxiety between couples. To find out the association between level of knowledge withselected demographic variable.Methods: The present study is a cross sectional non experimental descriptive survey. The total samplesfor this study are 380 primi couples. A self-structured questionnaire was prepared to assess the level ofknowledge of primiparus couples and standardize anxiety tool to assess anxiety between parents. Data wascollected by interviewing the study samples. Pilot study was conducted with 30 samples from differentsettings to check the reliability & feasibility of the study.Results: The finding of this study is (29%) of couple has good knowledge and (37%) couple has poorknowledge regarding preparedness of parenthood. Mean and SD of knowledge score of father and mother is17.06±3.60 and 18.36±3.99 respectively. More than half i.e. 41.31% couple has mild to moderate anxiety andonly 42.89% couple has minimum anxiety. There is no significant association between level of knowledgeand age, occupation, level of education and monthly income of couple as it is less than P value 0.05.